1989
DOI: 10.1247/csf.14.731
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new endothelial cell growth factor (f-ECGF) partially purified from the supernatant of human fibroblast cells.

Abstract: ABSTRACT. A new endothelial cell growth factor (f-ECGF) was partially purified from the cultured medium of human fibroblast cells of embryonic lungs. The partially purified f-ECGF induced neovascularization in rabbit cornea. It showed a selective growth stimulatory activity on the endothelial cells in vitro, whereas acidic-and basic-fibroblast growth factors (a-and b-FGFs) showed a broad spectrum of growth stimulation among tissues or cells. f-ECGF did not compete with the binding of a-FGF to the cell surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Some of these cells stained for alpha-smooth muscle actin and, when isolated, showed morphological features of myofibroblasts. Consistent with the observations that expression of TSP is enhanced by fibroblasts and smooth muscle cell mitogens (10,12), that antibodies against TSP inhibit growth of rat aortic smooth muscle ceils (14), and that TSP stimulates the growth of fibroblasts ( growth factor(s) as previously described (32,33). Myofibroblasts may promote angiogenesis also by producing extracellular matrix molecules required by the endothelial cells (32).…”
Section: Discussionsupporting
confidence: 85%
“…Some of these cells stained for alpha-smooth muscle actin and, when isolated, showed morphological features of myofibroblasts. Consistent with the observations that expression of TSP is enhanced by fibroblasts and smooth muscle cell mitogens (10,12), that antibodies against TSP inhibit growth of rat aortic smooth muscle ceils (14), and that TSP stimulates the growth of fibroblasts ( growth factor(s) as previously described (32,33). Myofibroblasts may promote angiogenesis also by producing extracellular matrix molecules required by the endothelial cells (32).…”
Section: Discussionsupporting
confidence: 85%
“…It therefore follows that rapid cell migration onto the luminal surface of the graft would be advantageous in preventing graft occlusion. 19,37,40 The velocity of cell migration is dependent on the structure of the luminal surface and biocompatibility of the synthetic material. 26,37,40,41 In this study, we demonstrated that the velocity of neointimal cell migration onto the Data presented as percentages.…”
Section: Discussionmentioning
confidence: 99%
“…19,37,40 The velocity of cell migration is dependent on the structure of the luminal surface and biocompatibility of the synthetic material. 26,37,40,41 In this study, we demonstrated that the velocity of neointimal cell migration onto the Data presented as percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Acidic fibroblast growth factor has also been known to stimulate proliferation and migration of vascular endothelial cells (Baudinet al 1990;Reygrobellet et al 1991). It has been already shown that endothelial cell growth factor (ECGF) stimulates severe neovascularization when applied into the rabbit cornea (Satoh et al 1989).…”
Section: Discussionmentioning
confidence: 99%